Gender roles and gender stereotypes in teaching literature - Gordić-Petković Vladislava (Temida)
Gender, identity and sexuality have to be more closely integrated into the broader discussion of literature and language, which can be achieved only through wider application of literary texts in the teaching process. Teaching literature to students of English serves not only the purpose of building an understanding of the human experience, but also tackles the issues of femininity and masculinity and helps sensitize the students to the gender differences and the codes of patriarchal society which result in male dominance. Poems by Emily Dickinson, Sylvia Plath and Anne Sexton have proved as valuable texts in teaching gender, as will be discussed in the paper, which focuses on Plath‘s „Lady Lazarus” and the strategies the educator can select in order to achieve the desired objective.